Computer modelling of the flow structure in a combined mixer for aqueous suspensions with solid and gas phases - Toister , Ruslan; Khrapach, Anton (Academic journal Industrial Machine Building Civil Engineering, 2024)
Computer modeling of multiphase flows in mixers for aqueous suspensions with solid and gas phases opens up new opportunities for optimizing mixing processes in industry. The creation of CFD-DEM models allows taking into account the interaction of liquid, solid and gas phases, fixing the features of circulation, mass transfer and rheological behavior of the medium. The article considers the features of the formation of the flow structure in a combined-type mixing chamber, analyzes the nature of changes in turbulent and convective processes in the presence of a gas phase and solid inclusions, and also substantiates approaches to building effective mixing modes.
Keywords: CFD-DEM modeling; multiphase flows; combined mixer; mass transfer; gas bubbles; circulation structures